(untitled) (Contemporary Journal of Social Science Review, 2025)
Urban mobility patterns react substantially to fuel price changes because these price changes force commuters to alter their travel modes and trip frequencies and their complete transport behaviors. The development of public transport infrastructure in Lahore city provides a setting where fuel cost increases trigger substantial changes in how people commute. Travel patterns in the Baghbanpura and Begumpura neighborhoods receive analysis regarding their response to changing fuel prices because these surroundings connect directly to the Orange Line Metro. The study explores how elevated fuel prices affect personal automobile usage together with public transportation dependency and ridesharing adoption and analyzes how income level and career status influence travel preferences. The research study integrated both survey tools for statistical evaluation in SPSS as well as MATLAB-based computational modeling for simulation analysis. SPSS measured the connection between fuel price alterations and travel patterns and MATLAB executed predictive analyses to predict future changes in vehicle ownership and public transport adoption. The research shows that higher fuel expenses decrease travel outings yet automobile ownership remains in upward trend because of limited price sensitivity against car dependency. Lower-income populations show greater sensitivity to price change than higher-income groups which makes them more likely to opt for public transport but the higher-income population is less impacted. Urban sustainability requires multiple transportation improvements because this research demonstrates that city authorities must enhance public transportation effectiveness as well as support bicycle walking and provide vehicle efficiency rewards. The research findings provide essential guidance for government officials to establish integrated transportation approaches which combine financial suitability with long-term urban development in Lahore together with similar fast-growing cities.